Mobile Application Architecture Restructuring with Microservice Approach - Nugraha, Ardiono Roma; Talita, Aini Suri (Journal of Information Technology and Computer Science, 2020)
Microservice is an architecture that can solve many problems in a monolithic architecture. One of the problems is the ability to handle many concurrent users. The existing monolithic application can be restructured into microservices to increase robustness in handling a lot of users, without exception native mobile application. This study aimed to restructure the existing native mobile application named TemanBisnis into microservices. The restructuring process can be done by splitting the application features according to its business domain into one service. Two microservice architecture designs were proposed in this study, named 3-1 architecture and 2-1-1 architecture. Both architectures can handle up to 100 concurrent users, although they start to produce errors. By performance, the 3-1 architecture is better than the 2-1-1 architecture. In the end, an existing native mobile application can be restructured into microservices. The 3-1 architecture should be adopted to achieve the best results between these two architectures.